Epilepsy - Cascino, Gregory D. (Henry Stewart Talks, 2014)
Epilepsy overview (Epidemiology, History, Economic burden, Co-morbidity, Improvement in quality of life, Adverse effects), Reasons for epileptic seizures, MRI images and recordings of epileptic seizures, Epilepsy in resource-poor countries, Focal (partial) epilepsy, Substrate-directed pathology (Tumors, Vascular anomalies, Malformations of cortical anomalies, Mesial temporal sclerosis), PET and glucose metabolism in focal epilepsy, MRI & Inter-ictal PET study, Treatment (Goals, strategies & Efficacy), Epilepsy surgery, Long-term and seizure-free surgical outcomes, Intractable epilepsy, Temporal & Extratemporal lobe epilepsy, Non-lesional epilepsy, SPECT & SISCOM imaging, Usage of FDG-PET, Image-guided laser thermal ablation, Electronic stimulation (Neuro Pace Responsive Neurostimulator System & SANTE), Update interview: Stereoelectroencephalography (SEEG), Update interview: Laser ablation, Update interview: Radiofrequency ablation, Update interview: Plan the operative strategy for resective surgery, Update interview: The expanded role of intracranial neuromodulation therapy, Update interview: Magnetoencephalography (MEG) in the preoperative assessment
Updated at 2020/09/22